A Jesuit Perspective on Metaphors for COVID-19 in the Online Journal "Thinking Faith " - Pasaribu, Truly Almendo; Dewi, Novita; Bram, Barli (Respectus Philologicus, 2021)
This article investigated how metaphors for COVID-19 were framed in a Catholic-based journal Thinking Faith. Data, consisting of 107 metaphors, were collected from the online journal and were analyzed within the Jesuit perspectives. Results showed that out of the 107 occurrences of metaphoric expressions for the pandemic, the source domains tend to have reflective and empowering aspects. The 12 main source domains of COVID-19 were war, drama, tools, natural forces, journey, manageable item, teacher, other living beings, darkness, pain, threat, and signs of the times. The coverage of Thinking Faith aimed to show the life-changing wisdom of the Gospel, Catholic Social Teaching, and Papal messages. Positive or neutral word choices of metaphors like teacher, drama, journey, manageable items, natural forces, and signs of the times managed to spark hopefulness for the journal readership. Meanwhile, the violence-related metaphors war, pain, and threat may appear to be discouraging. Overall, the metaphors used in the Jesuit online journal were contextually heartening